2020
DOI: 10.1093/cvr/cvaa286
|View full text |Cite
|
Sign up to set email alerts
|

Tc17 CD8+ T cells accumulate in murine atherosclerotic lesions, but do not contribute to early atherosclerosis development

Abstract: Aims CD8+ T-cells can differentiate into subpopulations that are characterized by a specific cytokine profile, such as the Tc17 population that produces IL-17. The role of this CD8+ T-cell subset in atherosclerosis remains elusive. In this study, we therefore investigated the contribution of Tc17 cells to the development of atherosclerosis. Methods and Results Flow cytometry analysis of atherosclerotic lesions from apoE-/- mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“… 39 Moreover, in vitro studies show that IL-17 can induce and stimulate the cells involved in atherosclerosis (macrophages, dendritic cells, vascular smooth muscle cells), thus causing inflammatory damage and apoptosis. 36 , 38 Our results confirm these immune-related pathways are closely related to CAD, indicating their importance. However, the specific mechanisms by which these immune pathways and their involved inflammatory cytokines and chemokines participate in the occurrence of CAD still need further research.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“… 39 Moreover, in vitro studies show that IL-17 can induce and stimulate the cells involved in atherosclerosis (macrophages, dendritic cells, vascular smooth muscle cells), thus causing inflammatory damage and apoptosis. 36 , 38 Our results confirm these immune-related pathways are closely related to CAD, indicating their importance. However, the specific mechanisms by which these immune pathways and their involved inflammatory cytokines and chemokines participate in the occurrence of CAD still need further research.…”
Section: Discussionsupporting
confidence: 80%
“… 35 , 36 Th2 cells can antagonize atherosclerosis by secreting interleukin (IL)-4 and IL-10. 37 , 38 The proportions of Th17 and its secreted IL-17 in CAD and atherosclerosis are increased, and positively correlated with the severity of the disease. 34 Previous clinical studies have found that the expression of Th17 and IL-17 in peripheral blood of patients with acute coronary syndrome is increased compared with patients with stable angina pectoris and chest pain syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CD8 + T cells can differentiate into subpopulations with specific cytokine profiles. CD8 + Tc17 T cells do not affect the development of early AS although they accumulate in the lesioned areas of mice with AS ( van Duijn et al, 2021 ). In contrast, CD8 + IFN-γ + T cells mediate the upregulation of immune responses and secretion of pro-inflammatory cytokines during the progressive phase of AS, exacerbating AS load and promoting the inflammatory response ( Li et al, 2023 ).…”
Section: Role Of Immune Cells In Asmentioning
confidence: 99%